2022
DOI: 10.3390/plants11030311
|View full text |Cite
|
Sign up to set email alerts
|

Lavandula dentata L.: Phytochemical Analysis, Antioxidant, Antifungal and Insecticidal Activities of Its Essential Oil

Abstract: Antioxidant, antifungal and insecticidal activities of essential oil (EO) extracted from the Moroccan lavender (Lavandula dentata) were investigated and their chemical constituents determined. Gas chromatography with flame ionization detection (GC-FID) and gas chromatography-mass spectrometry analyses (GC-MS) were used to examine the phytochemical composition of EO. Antioxidant potential was examined in vitro by use of three tests: DPPH inhibition, reducing power (FRAP) and total antioxidant capacity (TAC). An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 45 publications
3
19
0
Order By: Relevance
“…A. biennis contained more (E)-β-farnesene (40%), (Z)-β-ocimene (34.7%), acetylenes (11.00%) (Z)-and (E)-en-yn-dicycloethers. Phenylpropanoids (16.2%) and methyl eugenol were the primary components of the EO from A. dracunculus (35.8%) [27,28]. Several studies indicated that A. aragonensis was characteristically distinguished by the presence of potentially bioactive compounds including chrysantenone and davanone [26,29,30], which are absent in our plant that was collected from the southern slope of Jbel Bou-Naceur.…”
Section: Chemical Composition Identification Of the Essential Oilmentioning
confidence: 80%
See 1 more Smart Citation
“…A. biennis contained more (E)-β-farnesene (40%), (Z)-β-ocimene (34.7%), acetylenes (11.00%) (Z)-and (E)-en-yn-dicycloethers. Phenylpropanoids (16.2%) and methyl eugenol were the primary components of the EO from A. dracunculus (35.8%) [27,28]. Several studies indicated that A. aragonensis was characteristically distinguished by the presence of potentially bioactive compounds including chrysantenone and davanone [26,29,30], which are absent in our plant that was collected from the southern slope of Jbel Bou-Naceur.…”
Section: Chemical Composition Identification Of the Essential Oilmentioning
confidence: 80%
“…A. biennis contained more (E)-β-farnesene (40%), (Z)-β-ocimene (34.7%), acetylenes (11.00%) (Z)- and (E)-en-yn-dicycloethers. Phenylpropanoids (16.2%) and methyl eugenol were the primary components of the EO from A. dracunculus (35.8%) [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our findings agreed with those reported in the literature linking the antibacterial potency of EOs to the relative proportions of camphor present [ 38 ], which proves that monoterpenes have antibacterial properties against a variety of microorganisms [ 39 ]. Terpene-rich EOs can easily cross bacterial cell walls and the cytoplasmic membrane, resulting in polysaccharide and phospholipid permeability disorders, which may lead to immediate bacterial death [ 40 ]. The molecular interaction of EO components with the bacterial membrane results in serious lesions, which might explain their antibacterial activity.…”
Section: Resultsmentioning
confidence: 99%
“…These results were comparable to EOs from Dittrichia viscosa , which revealed 192 μ g AAE/mg as TAC [ 26 ]. In addition, the EOs of the leaves of Lavandula dentata scored 81.28 μ g AAE/mg [ 27 ]. EOs from Withania frutescens also scored 91 μ g AAE/mg [ 14 ].…”
Section: Resultsmentioning
confidence: 99%